Screening and treating pulmonary arterial hypertension in a tertiary hospital‐based multidisciplinary clinic: the first 200 patients. Issue 1 (17th January 2013) - Low, A. J.; Fowler, D.; Manghani, M. K.; Young, I.; Garsia, R.; Torzillo, P.; Youssef, P.; Celermajer, D. S.
Abstract Background Pulmonary arterial hypertension (PAH) is an increasingly recognised serious illness with insidious onset, delayed diagnosis, complex diagnostic algorithms and poor prognosis, but with recently available effective treatments. Aims To efficiently diagnose and to offer treatment for PAH, we established a multidisciplinary service in 2005, where patients attend a clinic staffed by specialists in cardiology, respiratory medicine, rheumatology and immunology in a tertiary referral hospital setting. Methods We studied the first 200 patients referred. Serology, echocardiography, lung function tests, high‐resolution computed tomography, World Health Organisation Class determination and 6‐min walk tests and/or right heart catheterisation were performed, as clinically indicated. Results Of the 200 patients seen, 66 had confirmed pulmonary hypertension (mean pulmonary artery pressure > 25 mmHg) diagnosed on echocardiography ± right heart catheterisation. Of these patients, 58 had catheter‐proven PAH (mean pulmonary artery pressure > 25 mmHg with mean wedge pressure < 15 mmHg). Underlying diagnoses for the confirmed PAH patients were idiopathic (32), scleroderma‐associated (14), other connective tissue disease (4) and associated with congenital heart disease (8). Patients with confirmed PAH were commenced on PAH‐specific therapy – initially bosentan in the majority but sildenafil, and iloprost were occasionally used initially for patient‐specific reasons. Median time from when the patient first called the clinic to prescription of therapy was 16 days (interquartile range; 0–31 days). All surviving patients with PAH have attended for regular 6‐monthly follow‐up visits with a 100% retention rate up to 4 years. Conclusion A multidisciplinary clinic can provide efficient diagnosis and rapid triage to PAH‐specific therapy, if appropriate. Retention rates remain high, at follow up.